2023
DOI: 10.1097/rct.0000000000001479
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Anemia From Cerebral Venous Sinus Attenuation on Deep-Learning Reconstructed Brain Computed Tomography Images

Abstract: The aim of the study is to evaluate whether the prediction of anemia is possible using quantitative analyses of unenhanced cranial computed tomography (CT) with deep learning reconstruction (DLR) compared with conventional methods. Methods:This cross-sectional retrospective study included 116 participants (76 males; mean age, 66.7) who had hemoglobin (Hb) levels obtained within 24 hours of unenhanced cranial CT, which included 2 reconstruction methods: DLR and hybrid iterative reconstruction. Regions of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…However, there also exist reports which reported the difference of CT attenuation of the liver between model-based iterative reconstruction and filtered back projection [ 23 , 24 ]. In addition, Yamakuni, et al recently reported that the CT attenuation of the cerebral venous sinus in DLR was significantly higher than that in Hybrid IR [ 25 ]; our results would be in line with their article.…”
Section: Discussionsupporting
confidence: 92%
“…However, there also exist reports which reported the difference of CT attenuation of the liver between model-based iterative reconstruction and filtered back projection [ 23 , 24 ]. In addition, Yamakuni, et al recently reported that the CT attenuation of the cerebral venous sinus in DLR was significantly higher than that in Hybrid IR [ 25 ]; our results would be in line with their article.…”
Section: Discussionsupporting
confidence: 92%
“…In a systematic review of abdominal CT with DLR, CT attenuation was reported to be similar with DLR and HIR [ 19 ]. However, according to Yamakuni et al, CT attenuation of the cerebral sinus was observed to be significantly different with DLR and HIR [ 21 ]. Our study results accord with the findings in the latter report.…”
Section: Discussionmentioning
confidence: 99%
“…In supervised training of DLR, low-quality data and high-quality images are respectively used as the input and reference data. A trained DLR is known to reduce image noise [ 19 ], thereby improving the quality of CT images in regions as varied as the head [ 20 , 21 ], chest [ 9 ], abdomen [ 10 , 19 , 22 , 23 ], and vertebrae [ 11 , 24 , 25 ]. We therefore hypothesized that DLR can also improve the quality of high-resolution CT of the temporal bone.…”
Section: Introductionmentioning
confidence: 99%
“…A higher interobserver agreement in the evaluation of ILD for DLR would have been resulted from an improved image quality. A better image noise reduction can be achieved compared to HIR in various regions such as the head, 19,27 vertebra, 21,23,24 and abdomen 20,22 as well as the chest. 25 Our study result corroborates with other studies, which revealed a significantly reduced quantitative image noise in DLR compared to HIR.…”
Section: Discussionmentioning
confidence: 99%